Lasiodiplodia species fungal osteomyelitis in a multiple myeloma patient. Issue 5 (9th September 2016) - Mohan, M.; Shalin, S.C.; Kothari, A.; Rico, J.C.C.; Caradine, K.; Burgess, M.
Abstract: Lasiodiplodia species are environmental fungi that have been reported as a cause of infection in both immunocompetent and immunocompromised patients. We present a case of fungal osteomyelitis caused by Lasiodiplodia species in a patient with multiple myeloma after autologous stem cell transplant. The patient was successfully treated with a combination of surgery and oral voriconzole. To the best of our knowledge, this is the first reported case of fungal osteomyelitis caused by Lasiodiplodia species.